Pengaruh Traits Personality dalam Pengambilan Keputusan Etis Auditor Internal: Studi Empiris pada Auditor BPKP Perwakilan Sumatera Barat - Aprinaldo, Rakel; Cheisviyanny, Charoline (Universitas Negeri Padang, 2025)
This study aims to explore the influence of personality traits on internal auditors ethical decision making, with a focus on auditors at the BPKP Representative of West Sumatra. Using quantitative methods, data were collected through questionnaires distributed to 46 auditors. The results of the analysis show that personality traits such as agreeableness, conscientiousness, extraversion, neuroticism, and openness to experience have varying impacts on ethical decision making. Specifically, this study found that personality traits of agreeableness and conscientiousness do not have a significant effect on the quality of auditors ethical decision-making. In contrast, more dominant personality traits, such as neuroticism, tend to negatively affect ethical decisions. These findings highlight the importance of self-awareness and ethical skill development among auditors, as well as the need for training that focuses on ethics and responsible decision making. This research is expected to contribute to the professional development of auditors and enhance integrity in audit practice, as well as strengthen public trust in the accounting profession.